The effects of bottom ash on setting time and compressive strength of fly ash geopolymer paste - Affandhie, B.A. (Institute of Physics Publishing, 2017)
This research is to find out the contribution of waste energy utilization of fly ash and bottom ash coal as binding agent of geopolymer concrete. This research methodology uses experimental approach in laboratory by making cylinder paste test object with dimension diameter of 2.5 cm x height 5 cm with some combination of fly ash and bottom ash mix with time setting test (ASTM C 191-04a) and compressive strength (ASTM C 39-04a). The research concludes that the effect of bottom ash on fly ash-based geopolymer paste shows good results in setting time and compressive strength. © Published under licence by IOP Publishing Ltd.